Basic Arduino Programming Training For High School Students - Aan Darmawan; Ratnadewi Ratnadewi; Erwani Merry Sartika; Novie Theresia Br. Pasaribu; Riko Arlando (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2017)
Electronic devices have become a part of human life today that can not be ignored. Community Service Program conducted by Prodi Electrical Engineering, Maranatha Christian University aims to increase knowledge, increase interest, form the ability of cooperation, improve creativity and improve the fighting power of high school students on the operation of electronic devices, in the form of arduino programming training . Arduino is an open source electronic kit specifically designed as a controller that regulates the working process of electronic circuits. The method used in this PKM is Participatory Action Research (PAR) in the form of lecture method to describe the material that has been prepared by PKM team, the method of practice in the form of Arduino programming and assembling the electronic component connected with Arduino, the method of mentoring when the students do the programming and stringing electronic components, and discussion methods in the form of inter-group cooperation to solve the case given. The results of this training can be a provision for high school students in the form of programming skills, the ability to assemble electronic components, the ability to work with groups to solve existing problems, and increase confidence in designing and operating electronic devices